Enantioselective Labeling of Zebrafish for D-Phenylalanine Based on Graphene-Based Nanoplatform - Yuqing He; Ziqi Ye; Fei Zhu; Tianxiang Qiu; Xiyan Dai; Yue Xie; Shibiao Zou; Qingjian Dong; Weiying Zhang; Junkai Ma; Xiaowei Mao (Molecules, 2023)
Enantioselective labeling of important bioactive molecules in complex biological environments by artificial receptors has drawn great interest. From both the slight difference of enantiomers’ physicochemical properties and inherently complexity in living organism point of view, it is still a contemporary challenge for preparing practical chiral device that could be employed in the model animal due to diverse biological interference. Herein, we introduce γ-cyclodextrin onto graphene oxide for fabricating γ-cyclodextrin and graphene oxide assemblies, which provided an efficient nanoplatform for chiral labelling of D-phenylalanine with higher chiral discrimination ratio of KD/KL = 8.21. Significantly, the chiral fluorescence quenching effect of this γ-CD-GO nanoplatform for D-phenylalanine enantiomer in zebrafish was 7.0-fold higher than L-isomer, which exhibiting real promise for producing practical enantio-differentiating graphene-based systems in a complex biological sample.